Teacher resilience in vulnerable contexts: a descriptive review of the literature - Durand Mercado, Jean (2022)
Objective. The present research aims to analyze the individual, organizational and community resilience of teachers in vulnerable contexts from a descriptive review of the literature. Methods. For the data collection process, the databases Scielo, Scopus, Proquest, Web of Science (WoS), ScienceDirect were used, 20 original research articles published between 2015 and 2021 were selected, including quantitative and qualitative articles. The inclusion criteria were: articles from vulnerable contexts, stress situations, COVID-19 pandemic, poverty situation, natural disasters, among others; and as an analysis strategy, they were ordered in a conceptually manner and by categories, the results were classified and the concepts were compared, in order to be written and presented. Results. Resilience is an aptitude for sustainability, coping and recovery in adversity situations that includes abilities such as: flexibility, adaptability, vulnerability, ingenuity, agility, redundancy, strength, tolerance and collaboration. A resilient teacher transmits a good organizational climate and culture; a resilient teacher within a vulnerable context transmits coping tools to his students, together with his personal resources, becoming a participant and promoting resilience within the community in which he develops. Conclusions. It is concluded that resilience is an ability to overcome obstacles and be able to adapt favorably, allowing the teaching professional to act positively in the climate and institutional culture, so it needs to be developed and encouraged by state organizations to be passed on to the student community (parents, teachers and students).